Immunoglobulin A Nephropathy and Malaria falciparum Infection; a Rare Association - Mahmoud Rafieian-Kopaei; Hamid Nasri; Farshid Alizadeh; Behrooz Ataei; Azar Baradaran (Tehran University of Medical Sciences, 2013)
Glomerular involvement occurs as a rare form of renal manifestation in Plasmodium falciparum malaria. Here, we report a rare case of falciparum malaria-associated IgA nephropathy. A 28-year-old man was admitted because of fever and abdominal pain. Ultrasound and computed tomography (CT) showed right kidney pyonenphrosis. Despite placing a nephrostomy tube, fever continued. Repeated CT was in favor of focal pyelonephritis. In addition, peripheral blood smear suggested malaria. Anti-malarial drugs were initiated and right nephrectomy was performed. One year after recovery from malaria, a persistent rise in serum creatinine was detected. A left kidney biopsy showed mesangial proliferation and dominant IgA deposits in immunofluorescence study while C1q was not deposited. The impression was IgA nephropathy with M1E0S0T0 of Oxford classification. The patient was prescribed a combination of low dose prednisolone and angiotensin converting enzyme inhibitor. Six months after treatment serum creatinine decreased from 1.6 mg/dL to 1.3mg/dL and urine abnormalities were disappeared. Our findings suggest that malaria infection might be associated with IgA nephropathy.